Optical Waveguides: Flexible Transient Optical Waveguides and Surface‐Wave Biosensors Constructed from Monocrystalline Silicon (Adv. Mater. 32/2018). Issue 32 (6th August 2018) - Bai, Wubin; Yang, Hongjun; Ma, Yinji; Chen, Hao; Shin, Jiho; Liu, Yonghao; Yang, Quansan; Kandela, Irawati; Liu, Zhonghe; Kang, Seung‐Kyun; Wei, Chen; Haney, Chad R.; et al.
Abstract : In article number1801584, Weidong Zhou, John A. Rogers, and co‐workers report flexible, transient optical waveguides constructed from monocrystalline silicon, for precise delivery of light to targeted biological tissues, at dimensions that can approach those of a single cell, with the ability to undergo controlled bioresorption into benign products after a well‐defined operational time, thereby serving as building blocks for silicon‐based bioresorbable photonic systems, with potential broad applicability in diagnosis and therapy.